My Utopia - Che, Onejoon; Fendler, Ute (Asia-Africa- Multifaceted Engagement in the Contemporary World, 2024)
During the hybrid conference “Multifaceted Relations: Africa–Asia,” which took place in July 2021 at the University of Bayreuth, the film My Utopia by South Korean artist Onejoon Che was screened. The projection was followed by a lively discussion, full of questions about the concepts underpinning the film. In order to capture and retain some of these ideas, this chapter is built on three parts: (1) the description of the project by Onejoon Che himself; (2) a transcription of a written interview, during which the interviewer, Ute Fendler, tries to address the main questions raised in the discussion that followed the screening to yield more information about and insight on the film, which resembles both a theater play and docufiction.